ANALISIS FAKTOR DETERMINAN MINAT PENGGUNAAN FINTECH PEER TO PEER LENDING SYARIAH SEBAGAI ALTERNATIF PERMODALAN UMKM DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Adi, Rizal Purnama (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
MSMEs have a crucial role in the economic growth of Indonesia, but their potential is not fully realized due to various challenges. One such challenge is the difficulty faced by MSMEs in securing business capital from traditional financial institutions due to complex requirements. However, the fintech industry, particularly sharia peer to peer lending, is rapidly growing in Indonesia and can serve as an alternative source of capital for MSMEs. This study aims to explore the factors influencing MSME players' interest in utilizing sharia peer to peer lending fintech, using the Technology Acceptance Model (TAM) as a framework. The research employed a quantitative approach, with the target population being MSME players in DKI Jakarta who were using the Qazwa application. The study took place from November 2023 to March 2024 and utilized the Partial Least Square (PLS) analysis tool with the SmartPLS 4.3.3 software. The findings indicate that perceived ease of use, perceived usefulness, subjective norm, and output quality all positively and significantly impact the interest of MSME players in using Qazwa as a sharia peer to peer lending fintech.